Peningkatan Kemampuan Pemahaman Matematis dan Self Confidence Melalui Pembelajaran Kooperatif Tipe Group Investigation pada Siswa Sekolah Dasar - Edison Edison; Sowanto Sowanto (Program Studi Pendidikan Matematika, 2021)
This study aims to analyze the increase in students' mathematical understanding ability and self-confidence as a result of the application of group investigation type cooperative learning. This research is quasi-experimental research, with the design used being